STUDENTS' PERSPECTIVE ON VIDEO CONFERENCING IN DISTANCE EDUCATION - Iscioglu, Ersun; Kaya, Omer Sami (Iated-Int Assoc Technology Education & Development, 2013)
The main aim of this research is to investigate students' opinions on video-conferencing in distance education. In this study, smart classroom is designed as a learning environment for students and the instructor is connecting to the class through video conferencing from a different country. This study is designed as a qualitative study. This research is realized by offering the course Scientific Research Methods in spring semester 2012-2013 by the Faculty of Education, at the Eastern Mediterranean University. A total of 20 students participated in the study. The data is gathered by focus group interviews, open-ended questions and observation. The data obtained in this study, will be analyzed using descriptive analysis. As a result of this study, it is determined that students believe that such applications are beneficial in many aspects and should definitely be used in teaching.
6th International Conference on Education, Research and Innovation (ICERI) -- NOV 18-20, 2013 -- Seville, SPAIN
Keywords: Video Conferencing; Smart Classroom; Distance Education; Student Opinions; Video Conferencing in Distance Education